Comprehensive assessment of rural environmental sanitation for 25 prefectures/counties/districts in and outside the Yellow River Basin, Shandong province - principal component and TOPSIS analysis - Xiao ZHANG; Xuting YANG; Yanxin GAO; Yinglin DU; Yuanyuan JIANG; Wen SUN; Feng SHI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo comprehensively assess rural environmental sanitation of 25 prefectures/counties/districts in and outside the Yellow River Basin, Shandong province for developing strategies on improvement of rural environmental sanitation. MethodsWe collected monitoring data of 2021 on rural environment sanitation of 25 prefectures/counties/districts of Shandong province; the 13 regions located at the Yellow River Basin were set as cases and the 12 regions outside the basin as controls. Principal component analysis and technique for order preference by similarity to an ideal solution (TOPSIS) analysis was adopted in the assessment. Nine positive high performance indicators were introduced to fit the evaluation model. Regional-specific standardized distance between the scores of each of the nine indicators and optimal ideal solution was utilized to evaluate rural environment sanitation of the 25 prefectures/counties/districts and comprehensive evaluation index was calculated for each of the 25 regions using Euclidean distance approximation method to determine ideal points through TOPSIS. ResultsThe nine core indicators included in the principal component analysis were region-specific annual net income per capita for farmers, annual net income per capital for all rural residents, county-level investment in rural environmental health, construction rate of comprehensive improvement projects for rural sanitation, construction rate of environment sanitation management system, prevalence of sanitary toilet, coverage of centralized rural water supply, transfer ratio of solid waste in rural areas, and transfer ratio of domestic sewage in rural areas. The three identified principal components for rural environment sanitation evaluation were economic condition, sanitation management, and primary health facilities, with the eigenvalues of 2.109, 2.076, and 1.349 and a cumulative contribution rate of 61.485%. Among the top five prefectures/counties/districts with higher values of comprehensive evaluation index, two were located in the Yellow River Basin (Huantai county and Shouguang prefecture, with the scores of 0.705 and 0.665) and three were outside of the basin (Rongcheng, Yanzhou and Gaomi prefectures, with the scores of 0.758, 0.687, and 0.662, respectively). Among the three identified principal components, the score for economic conditions showed the highest coefficient of variation (CV, 0.481) for the regions in the Yellow River Basin; while, the score for rural environmental sanitation management showed the lowest CV (0.114). ConclusionIn rural Shandong, the sanitation management and primary health facilities are better in the regions in the Yellow River Basin but the contribution of the economic situation to the comprehensive index for environment sanitation evaluation is relatively low compared to those in the regions outside of the basin.